Impact of Registered Dietitian Expertise in Health Guidance for Weight Loss - Imanaka, Mie (PLoS One, 2016)
BACKGROUND & OBJECTIVES: Expertise of registered dietitians (RDs) is important for health guidance but has been poorly evaluated. We evaluated the kind of RD expertise that would improve their skills. DESIGN, SETTING, PARTICIPANTS, MEASUREMENTS: This study was a post-hoc analysis of our randomized controlled trial, which compared the weight change between participants using the web-based self-disclosure health support and those using the email health support. Healthy men and women aged 35–64 years with a body mass index (BMI) of > = 24.5 kg/m(2) were recruited for this study. We evaluated the relationship of RD expertise indicators including the duration of working as an RD, the experience of health counseling, and membership in the Japan Dietetic Association (JDA) with the weight loss of study participants. The primary endpoint was the change in body weight. Comparison of changes in body weight by the RD expertise indicators was evaluated using analysis of covariance. RESULTS: A total of 175 participants were eligible for analyses. Changes in body weight were significantly greater when they were supported by the RDs in the routine counseling group than when supported by the RDs in the non-routine counseling group (-1.8 kg versus -0.4 kg, fully adjusted P = 0.0089). Duration of working as an RD and JDA membership did not significantly affect changes in body weight. CONCLUSIONS: Among some indices of RD experience, the experience of providing routine experience of health counseling was associated with weight loss.